2015
DOI: 10.1063/1.4927579
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless microtearing modes in hot tokamaks: Effect of trapped electrons

Abstract: Collisionless microtearing modes have recently been found linearly unstable in sharp temperature gradient regions of large aspect ratio tokamaks. The magnetic drift resonance of passing electrons has been found to be sufficient to destabilise these modes above a threshold plasma β. A global gyrokinetic study, including both passing electrons as well as trapped electrons, shows that the non-adiabatic contribution of the trapped electrons provides a resonant destabilization, especially at large toroidal mode num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These MTMs are fundamentally different to the low k y MTMs as they will be shown to be unstable in the collisionless regime, which have been found previously [35,43,44], though the driving mechanisms are not completely understood.…”
Section: Low K Y Kbmmentioning
confidence: 57%
“…These MTMs are fundamentally different to the low k y MTMs as they will be shown to be unstable in the collisionless regime, which have been found previously [35,43,44], though the driving mechanisms are not completely understood.…”
Section: Low K Y Kbmmentioning
confidence: 57%
“…In particular, models based off of KBM constraints have been extensively developed and are able to reproduce observed pedestal heights and widths to within ∼ 20% on many machines [6,7]. However, ongoing gyrokinetic work has suggested that other modes, especially the MTM [9][10][11][12], may also contribute to transport mechanisms in the pedestal region, potentially having large effects on energy regulation [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Examining the impact of collisions on the high k y MTM, it can be seen from Figure 14c that these are collisionless MTMs, highlighting the completely different nature of these modes compared to the longer wavelength MTMs. Collisionless MTMs have been seen before [35,43,44,52], but their mechanism is not fully understood. These are weakly stabilised by collisions over the range of the scan, but it appears that the impact is not significant.…”
Section: Collision Frequencymentioning
confidence: 99%